Judicial training modules on environmental law : application of environmental law by national courts and tribunals (UNEP NairobiKE, 2007)
Contains ten PowerPoint presentations on several themes of special relevance to the adjudication of environmental disputes including the role of the judiciary in promoting the rule of law in the area of sustainable development; scope and content of national environmental law; how environmental law cases come before courts; managing environmental cases; evidence in environmental cases; remedies in environmental cases; and resolving environmental disputes.
Keywords: ENVIRONMENTAL LEGISLATION